Therapist self-compassion and compassion fatigue: the mediating role of resilience - Ruiz-Aranda, Desireé; García-Silva, Beatriz; Fenollar, Javier (Anales de Psicología / Annals of Psychology, 2024)
The demands placed on professionals working with psychological problems can result in a risk of burnout (Yang & Hayes, 2020). The objective of this study was to analyze the possible role of resilience as a mediator variable in the relationship between self-compassion and compassion fatigue, burnout, and compassion satisfaction. A descriptive cross-sectional study design was used. Sixty-five clinical psychologists (50 women and 15 men) aged between 23 and 71 years (M = 33.8, SD = 10.8) participated in the study. The therapists completed the Self-Compassion Scale, the 14-Item Resilience Scale, and the Professional Quality of Life Scale. Separate simple mediation models were tested to examine the extent to which each of the Resilience scale variables attenuated the relationship between Self-compassion and Professional Quality of Life. Serial multiple mediator models were performed to explore whether Resilience variables acted interactively as mediators in the association between Self-compassion and Professional Quality of Life. Simple mediation analyses showed that Personal Competence was a significant partial mediator in the relationship between Self-Compassion and Compassion Satisfaction and Burnout. Personal Competence and Acceptance of Self and Life were not significant mediators of the relationship between Self-Compassion and Secondary Traumatic Stress.